RHINOSINUSITIS IDENTIFICATION AND TRAINING OF CADRES IN MEDAN AREA DISTRICT - Farhat; E. Rahmi Daulay (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Objective : Chronic rhinosinusitis is an inflammation of the nasal mucosa and paranasalsinuses established based on a history of rhinosinusitis lasting more than 12 weeks. Rhinosinusitis may becaused by allergies, infections and anatomical structural abnormalities or other causes such as idiopathic,nasal, hormonal, drugs, irritant, fungi, emotions, atrophy. Lingkungan VIII and X Kelurahan Tegal Sari IMedan Area District was selected as a community service partner based on location and environmentcharacterized.Method : We trained the cadres to know rhinosinusitis and we screened the population to do early detectionof the disease.Result : From 100 patients who came, 56% of them are males, with most age 21-25 years as many as 36%,while the main complaint was runny nose as many as 43%.